2019
DOI: 10.1001/jamapediatrics.2018.4346
|View full text |Cite
|
Sign up to set email alerts
|

Association of Friday School Report Card Release With Saturday Incidence Rates of Agency-Verified Physical Child Abuse

Abstract: IMPORTANCE Corporal punishment is a leading risk factor for physical abuse. Strong anecdotal evidence from physicians and other professionals working in child protection suggest that punishment-initiated physical abuse for school-aged children increases after release of report cards. However, no empirical examination of this association has occurred. OBJECTIVE To examine the temporal association between school report card release and incidence rates (IRs) of physical abuse. DESIGN, SETTING, AND PARTICIPANTS Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… Barboza-Salerno (2019) , Barboza and Siller (2018) , Bright et al (2019) , Deccio et al (1994) , Employment Situation Summary (2020), Septembe , Freisthler et al (2005) , Fromm (2004) , Gelles (1993) , Griffith (2020) , Jones (2006) , Klein (2011) , Los Angeles Department of Public Health (2020a) , Maguire-Jack and Font (2014) , Martin and Walters (1982) , Sampson and Groves (1989) and U.S. Census Bureau (2020) .…”
Section: Uncited Referencesmentioning
confidence: 99%
“… Barboza-Salerno (2019) , Barboza and Siller (2018) , Bright et al (2019) , Deccio et al (1994) , Employment Situation Summary (2020), Septembe , Freisthler et al (2005) , Fromm (2004) , Gelles (1993) , Griffith (2020) , Jones (2006) , Klein (2011) , Los Angeles Department of Public Health (2020a) , Maguire-Jack and Font (2014) , Martin and Walters (1982) , Sampson and Groves (1989) and U.S. Census Bureau (2020) .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Previous studies have examined day of the week as a factor for abuse in older children. A recent study from 2018 identified higher rates of verified reports of child abuse in children 5–11 years old in the state of Florida on Saturdays immediately following a Friday report card release compared to Saturdays that did not follow a Friday report card release (Bright et al, 2019). Unlike the study performed by Bright et al, however, there was a fairly even distribution of AHT cases in this study among the days of the week with no increased rate of cases on weekends in comparison to weekdays (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this work provides insight into how acute and chronic stressors may translate into an increased risk of family violence and child maltreatment. Harsh parenting style with corporal punishment in the face of challenging child behavior or poor school performance may lead to child abuse and maltreatment ( Bright et al, 2019 ). Separately, the level of parenting stress is associated with physical child abuse potential ( Crouch & Behl, 2001 ).…”
Section: Discussionmentioning
confidence: 99%